Mathematical modeling study of school-based chlamydia screening: potential impact on chlamydia prevalence in intervention schools and surrounding communities - Minttu M. Rönn; Richard Dunville; Li Yan Wang; Meghan Bellerose; Yelena Malyuta; Nicolas A. Menzies; Maria Aslam; Felicia Lewis; Cherie Walker-Baban; Lenore Asbel; Sarah Parchem; Lisa Masinter; et al. (BMC, 2020)
Abstract Background Chlamydia screening in high schools offers a way to reach adolescents outside of a traditional clinic setting. Using transmission dynamic modeling, we examined the potential impact of high-school-based chlamydia screening programs on the burden of infection within intervention schools and surrounding communities, under varying epidemiological and programmatic conditions. Methods A chlamydia transmission model was calibrated to epidemiological data from three different settings. Philadelphia and Chicago are two high-burden cities with existing school-based screening programs. Rural Iowa does not have an existing program but represents a low-burden setting. We modeled the effects of the two existing programs to analyze the potential influence of program coverage and student participation. All three settings were used to examine a broader set of hypothetical programs with varying coverage levels and time trends in participation. Results In the modeled Philadelphia program, prevalence among the intervention schools' sexually active 15-18 years old population was 4.34% (95% credible interval 3.75-4.71%)after 12 program years compared to 5.03% (4.39-5.43%) in absence of the program. In the modeled Chicago program, prevalence was estimated as 5.97% (2.60-7.88%) after 4 program years compared to 7.00% (3.08-9.29%) without the program. In the broader hypothetical scenarios including both high-burden and low-burden settings, impact of school-based screening programs was greater in absolute terms in the higher-prevalence settings, and benefits in the community were approximately proportional to population coverage of intervention schools. Most benefits were garnered if the student participation did not decline over time. Conclusions Sustained high student participation in school-based screening programs and broad coverage of schools within a target community are likely needed to maximize program benefits in terms of reduced burden of chlamydia in the adolescent population.